"Pleasure stolen from the poor": Community discourse on the 'theft' of a Banksy. (December 2016) - Hansen, Susan
The removal of street art from community walls for private auction is a morally problematic yet legal action. This paper examines community reactions to the removal of Banksy's No Ball Games for private auction. Five hundred unique reader comments on online newspaper articles reporting this controversial event were collected and analyzed. An emerging set of urban moral codes was used to position street art as a valuable community asset rather than as an index of crime and social decay. The latter discourse informed a repertoire that depicted No Ball Games as unlawful graffiti that was rightfully removed. Here, the operations of 'the police' (Rancière, 1998: 17) in the distribution of the sensible are evident in the assertions that validate and depoliticize the removal of No Ball Games . This repertoire was used to attribute responsibility for the work's removal to deterministic external forces, while reducing the accountability attributable to those responsible for the removal of the work. A contrasting anti-removal repertoire depicted street art as a gift to the community, and its removal as a form of theft and a source of harm to the community. The pro-removal repertoire incorporates and depoliticizes elements of the anti-removal repertoire, by acknowledging the moral wrong of the removal, but yielding to the legal rights of the wall owners to sell the work; and by recognizing the status of street art as valuable, but asserting that the proper place for art is a museum. The anti-removal repertoire counters elements of the pro-removal repertoire, by acknowledging the illegality of street art, but containing this to the initial act of making unsanctioned marks on a wall, after which point the work becomes the property of the community it is located within. This analysis reveals an emergent set of urban moral codes that positions a currently legal action as a form of criminal activity.